FAKTOR FUNDAMENTAL YANG MEMPENGARUHI PERUBAHAN HARGA SAHAM (Studi Empiris pada Perusahaan Finansial yang Terdaftar Di BEI Tahun 2009dan 2010) - Bunga Maharani; Dwi Ratna Wulandari (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2013)
The objective of the study is to investigate the effect of free cash flow, return on equity, current ratio, firm size and net profit margin on dividend policy that measured by dividend payout ratio. The population of this study are all manufacturing companies listed on the Indonesian Stock Exchange (IDX).The period of this study are 2008-2011. Based on purposive sampling method, 19 companies were used on the study. The sample were gathered from annual reports and ICMD. This study used multiple linear regression as analysis method with 5% significant level. The results of the study indicate that free cash flow and return on equity have positive effect on dividend policy, while current ratio, firm size and net profit margin have no significant effect on dividend policy. Keywords: Dividend Policy, dividend payout ratio (DPR), free cash flow (FCF), return on equity (ROE), current ratio (CR), firm size (FZ) and net profit margin (NPM).